THE EFFECTS OF INTEGRATION BETWEEN KURIKULUM 2013 AND CAMBRIDGE CURRICULUM IN ENGLISH (STUDY CASE TAKEN FROM SAINT PETER'S JUNIOR HIGH SCHOOL) - Simanjuntak, Marudut Bernadtua (Study Program of English Literature, 2020)
Many schools in Indonesia have improved the quality of the English skills of the students. One way to improve and develop the curriculum which outlines the English skills is by doing curriculum integration. Saint Peter Junior High School which is located Kelapa Gading - North Jakarta has applied Kurikulum 2013 and Cambridge Curriculum for some years. The Cambridge curriculum approaches language skills and Kurikulum 2013 approach used was language competence which included grammar competencies, social competencies, and communicative competencies. Integration models that are compatible with the integration of both are nesting models. The research is aimed to show the effects of the Cambridge Curriculum which is integrated with Kurikulum 2013 in Saint Peter's Junior High School. Keywords: Curriculum Integration, Cambridge Curriculum, Kurikulum 2013, English